Actualization of Meaning from Bale to the Field in the Development of Youth Mushallah Nurul Ikhwan Ulujami's Morals - Achmad Muhajir; Rina Kurnia (CV ODIS, 2022)
There are many methods in youth development, such as youth scientific studies (KIR), OKP (youth organizations), youth studies, Pencak Silat, etc. These sectors can be used for coaching young people to minimize the negative treatment of youth. Something developing in the youth community of the Ulujami village is the youth recitation which is usually done in the mosque or prayer room. One of them is the Youth Mushollah Nurul Ikhwan (FORNI/ Youth Forum Mushallah Nurul Ikhwan) which is located at rw.03/rt 007 Ulujami sub-district which will be the object of research, using descriptive qualitative research methods. FORNI members are very heterogeneous, because FORNI does not only consist of teenagers/youth/homeschoolers, but many of them are youths who often hang out (tongkrongan children). Youth development with religious education such as reading the Qur'an for members who cannot read the Qur'an, morals, and fiqh material. To create a spirit of learning, the board of Forni held an additional activity, martial arts, every week. With additional activities in the form of art and culture, in this case, is silat Beksi, which of course, in Beksi, there is a ritual known as Rosulan or the cultivation of spiritual values ??to members/participants of Beksi Silat, which can influence strengthening the character of youth. And this is what is meant by the meaning of the bale to the field. From the bale, the youths learn to recite the Koran to decorate their souls with religious values, while in the field, the youths are physically training them with sports that can nourish their bodies. So here is the stretching point: to produce quality youth, you must combine physical and spiritual elements